Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

|3t – 9| = 3 Step by step

Sagot :

Answer:

t = {4, 2}

Step-by-step explanation:

|3t-9| = 3

Split into two parts,

3t-9 = 3, and -(3t-9) = 3

Solve

t-3 = 1, and -(t-3) = 1

t = 4, and -t+3 = 1

t = 4, and t=2